HUBUNGAN KEJADIAN INFEKSI Soil transmitted helminths (STH) dengan NILAI EOSINOFIL dan HEMOGLOBIN DARAH pada MASYARAKAT di KAMPUNG 1001 MALAM SURABAYA - Okvitasari Arin; Sasongkowati Retno; Anggraini Anita Dwi (Analis Kesehatan Sains, 2021)
Soil worm infection transmitted Helminths (STH) is a group of parasitic nematodes that cause infection in the human gut which is transmitted through contaminated soil eggs or larvae. STH often infects people with poor environmental sanitation and lack of public awareness of the importance of maintaining personal and environmental hygiene. An increase in the value of eosinophils and a decrease in the value of blood hemoglobin are markers of infection by the STH parasite. The purpose of this study was to determine the relationship between the incidence of soil-transmitted helminths (STH) infection with the value of eosinophils and blood hemoglobin in the 1001 night village community, Surabaya. This type of research is an analytical observational study and the samples in this study were blood and feces taken from the people of 1001 Malam Surabaya village as many as 25 people with a random sampling technique using the native method for stool examination and using a hematology analyzer for blood examination. Based on the results of research conducted on the 1001 night village community, it was known that the prevalence of worm infection was Ascaris lumbricoides. The prevalence of STH infection with eosinophilia was 15 samples. A significant relationship after being tested statistically with the Spearman Rank Correlation test was found between STH infection and the eosinophil value of 0.034. Then on the relationship between hemoglobin values and STH infection, a significant value was obtained, namely 0.00. There is a significant relationship between STH infection with the value of eosinophils and blood hemoglobin.